Sino-German Encounters and Entanglements
XVI, 344 p. 1 illus.
Keywords: Adopting a transnational approach, this edited volume reveals that Germany and China have had many intense and varied encounters between 1890 and 1950. It focuses on their cross-cultural encounters, entanglements, and bi-directional cultural flows. Although their initial relationship was marked by the logic of colonialism, interwar Sino-German relations established a cooperative relationship untainted by imperialist politics several decades before the era of decolonization. A range of topics are addressed, including pacifists in Germany on the Boxer Rebellion, German investment in Qingdao, teachers at German-Chinese schools, social and pedagogical theories and practice, female literary and missionary connections, Sino-German musical entanglements, humanitarian connections during the Nanjing Massacre, Manchukuo-German diplomacy, and psychoanalysis during the Shanghai exile. Joanne Miyang Cho is a Professor at the History Department of William Paterson University of New Jersey, USA.